Cross-cohort analysis of expression and splicing quantitative trait loci in TOPMed - Peter Orchard; Thomas W. Blackwell; Linda Kachuri; Peter J. Castaldi; Michael H. Cho; Stephanie A. Christenson; Peter Durda; Stacey Gabriel; Craig P. Hersh; Scott Huntsman; Seungyong Hwang; Roby Joehanes; et al. (Science, 2026)
Most genetic variants associated with complex traits are hypothesized to regulate gene expression. To understand the genetics underlying gene expression variability, we characterized 14,324 RNA-sequencing samples from the Trans-Omics for Precision Medicine program and performed expression and splicing quantitative trait locus (e/sQTL) analyses in six tissues and cell types, including whole blood ( n = 6454) and lung ( n = 1291). We detected tens of thousands of secondary cis-e/sQTLs, showing that secondary cis-e/sQTL discovery remains unsaturated. We fine-mapped UK Biobank–derived genome-wide association study (GWAS) signals from 164 traits and identified e/sQTL colocalizations for 10,611 GWAS signals, including 7096 that colocalize with secondary e/sQTLs. Our results suggest that even larger e/sQTL analyses will uncover additional secondary e/sQTLs, further benefiting GWAS interpretation.